DE-RADIKALISASI AGAMA DAN PENDIDIKAN KEARIFAN LOKAL PADA MAHASISWA UNIVERSITAS ANDI DJEMMA DI KOTA PALOPO - Zainuddin, Fauziah (PALITA: Journal of Social - Religion Research, 2016)
This article discussed about the perceptions ofÂ  Administration Department students at Andi Djemma University of Palopo on religious de-radicalization and local wisdom as well as the roles of local wisdom education among the students. To answer these problems, it surveiedÂ  50 out of 150 students of Administration Department at Andi Djemma University of Palopo. It was found that; a) the studentsâ perception level on local wisdom was categorized moderate. This category means that the respondents simply knew the terms of local wisdom based on their native language labelity, not the meaning or the substances. b) The studentsâ perception level on radicalism and de-radicalization was categorized moderate. This category tends to be close with radical. It means that the students conceptually knew about modern religious views that are rational and fundamental. However, they did not realize as a form of radicalism. c) The studentsâ perception level on the roles of local wisdom education regarding the de-radicalization was categorized good. It means that the lecturers integrated the local wisdom in the learning process. It adequately contributed to the development of studentsâ thinking that serves as a comparison in counteracting radical ideology to reach the consciousness of humanity.